Complete Inferior Rectus Transection Following Blunt Trauma: A Case Report and Novel Approach to Surgical Repair. Issue 3 (May 2019) - Tynan, Dominique; Dunn, Hamish; Roberts, Timothy
Abstract : Inferior rectus avulsion following blunt trauma is rare, with even fewer reported cases of complete transection. The authors report a case of orbital floor fracture and inferior rectus muscle transection without herniation following blunt orbital trauma. This case first highlights the difficulty in diagnosing complete inferior rectus muscle transection clinically and with imaging and second that an acceptable functional outcome can be achieved by a novel surgical repair approach utilizing contiguous orbital anatomical relations of the inferior oblique and inferior rectus muscles. Abstract : The case report describes complete inferior rectus transection following blunt trauma: a case report and novel approach to surgical repair.